Treatment of Chronic and Complicated Ruptures of the Rotator Cuff of the Shoulder - Strafun, O.S.; Sukhin, O.Yu.; Lysak, A.S.; Bohdan, S.V. (TERRA ORTHOPAEDICA, 2021)
Relevance. The etiology of ruptures of the rotator cuff of the shoulder (RC) is represented by a variety of diseases, including age-related degeneration, low- and high-energy trauma. Most often, a rupture of the RC, combined with trauma, occurs with anterior dislocation of the shoulder – in 56% of patients. The “terrible triad” of the shoulder, which leads to a loss of function and disability in patients, is diagnosed in 9-18% of patients. RC ruptures of <1-1.5 cm throughout the entire thickness of the tendon have a high risk of progression and formation of a massive rupture of the RC. According to various authors, massive ruptures occur in 40% of all RC ruptures.Objective: to evaluate the results of surgical treatment of patients with old and complicated ruptures of the RC.Materials and Methods. From 2016 to 2021, in the SI “Institute of Traumatology and Orthopedics of NAMS of Ukraine”, Department of Microsurgery and Surgery of the Upper Limb, 140 patients with a ruptured RC were treated. The patients underwent: suture of the RC under arthroscopic control, open RC suture, transposition of the latissimus dorsi tendon into the RC defect, implantation of biodegradable InSpace balloon, or implantation of a biomatrix into the RC defect and reverse shoulder arthroplasty.Results. The function was assessed before surgery and in the long-term postoperative period using the Constant-Murley Score. In 5 patients with an implanted balloon, the score increased from 34-38 to 56-61 in 8-12 months. In 7 patients with reinforced biomatrix implantation, the score increased from 34-38 to 65-69 in 9-12 months. In 7 patients with transposition of the latissimus dorsi tendon, the score increased from 35-37 to 68-75 in 9-12 months. In 10 patients with reverse arthroplasty, the score increased from 30-34 to 58-65 in 12-18 months. In 82 patients, after the suture of the RC under arthroscopic control of the shoulder, the score increased from 36-40 to 78-82 in 12-18 months. In 29 patients with an open suture of the RC, the score increased from 34-38 to 68-75 in 12-18 months.Conclusions. Early diagnosis and timely surgical treatment for the pathology of the RC make it possible to obtain the best results in the long-term postoperative period. Massive and old ruptures of the RC require a complete instrumental examination in the preoperative period. The degree of adipose degeneration and rotator arthropathy is of key importance for determining the operative tactics of surgical treatment.